2021
DOI: 10.15446/revfacmed.v69n2.85599
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of two muscle strengthening programs in patients with patellofemoral pain syndrome. A randomized controlled clinical trial

Abstract: Introduction: Patellofemoral pain syndrome (PFPS) is one of the most common musculoskeletal disorders affecting the knee joint. Conservative treatment reduces pain and improves functional capacity in the short and medium-term.Objective: To determine the therapeutic effect of two muscle strengthening exercise programs in patients with PFPS from Bogotá, Colombia, aged between 15 and 40 years.Materials and methods: Experimental randomized controlled clinical trial conducted in 40 patients with PFPS from Bogotá, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
0
1
Order By: Relevance
“…Our study results agreed with previous evidence reporting pain and disability improvements with exercise without EMS (Bily, Trimmel, Mödlin, Kaider, & Kern, 2008;Emamvirdi et al, 2019;Frye, Ramey, & Hart, 2012;Prieto-García, Cortés-Reyes, Lara-Cotacio, & Rodríguez-Corredor, 2021;Stensdotter, Hodges, Mellor, Sundelin, & Häger-Ross, 2003). Stensdotter et al pointed out the effects of open and closed-chain exercises on muscle activity and pain reduction in PFP (Stensdotter et al, 2003).…”
Section: Effect On the Pain And Disabilitysupporting
confidence: 93%
See 1 more Smart Citation
“…Our study results agreed with previous evidence reporting pain and disability improvements with exercise without EMS (Bily, Trimmel, Mödlin, Kaider, & Kern, 2008;Emamvirdi et al, 2019;Frye, Ramey, & Hart, 2012;Prieto-García, Cortés-Reyes, Lara-Cotacio, & Rodríguez-Corredor, 2021;Stensdotter, Hodges, Mellor, Sundelin, & Häger-Ross, 2003). Stensdotter et al pointed out the effects of open and closed-chain exercises on muscle activity and pain reduction in PFP (Stensdotter et al, 2003).…”
Section: Effect On the Pain And Disabilitysupporting
confidence: 93%
“…Stensdotter et al pointed out the effects of open and closed-chain exercises on muscle activity and pain reduction in PFP (Stensdotter et al, 2003). Prieto-García et al also showed the effects of two types of strength training depending on reducing pain in PFP (Prieto-García et al, 2021). Opposite to our results, Bily et al showed the effects of 12 weeks of exercise alone and with EMS to reduce pain in PFPs, but no significant effect was found by adding EMS (Bily et al, 2008).…”
Section: Effect On the Pain And Disabilitycontrasting
confidence: 60%